Study of bound states in 10Be by one neutron removal reactions of 11Be. (8th March 2017) - Johansen, Jacob G; Bildstein, V; Borge, M J G; Cubero, M; Diriken, J; Elseviers, J; Fraile, L M; Fynbo, H O U; Gaffney, L P; Gernhäuser, R; Jonson, B; Koldste, G T; et al.
Abstract: The bound states of 10 Be have been studied by removing single neutrons from 11 Be nuclei. A 2.8 MeV u –1 beam of 11 Be was produced at ISOLDE, CERN and directed on to both proton and deuteron targets inducing one-neutron removal reactions. Charged particles were detected to identify the two reaction channels ( d, t ) and ( p, d ), and the individual states in 10 Be were identified by gamma detection. All bound states but one were populated and identified in the ( d, t ) reaction. The combination of REX-ISOLDE and MINIBALL allowed for a clean separation of the high-lying states in 10 Be. This is the first time these states have been separated in a reaction experiment. Differential cross sections have been calculated for all the reaction channels and compared to DWBA calculations. Spectroscopic factors are derived and compared to values from the litterature. While the overall agreement between the spectrocopic factors is poor, the ratio between the ground state and the first excited state is in agreement with the previous measured ones. Furthermore, a significant population of the 2 2 + state is observed, which which may indicate the presence of multi-step processes at our beam energy.